ANDROID-BASED APPLICATION AS A MEDIA TO SUPPORT THE LEARNING AND PRESERVATION OF JAVA LANGUAGE FOR MI/SD STUDENTS - Nina Indriani; Siti Rodliyah Eka Agustina; Alifa Feby Nur Aini; Dita Dwi Cahyani (Auladuna: Jurnal Pendidikan Dasar Islam, 2023)
Abstract The development of the ABJA (Aku Isa Basa Jawa) application is intended to make Javanese language learning support media for elementary schools (SD) or Madrasah Ibtidaiyah (MI) students interesting and fun. In addition, the development of ABJA applications is also intended to preserve Javanese art and culture, which are now increasingly fading. This application was developed using the Multimedia Development Life Cycle (MDLC) model consisting of six stages. The data analysis technique used was a Likert scale to interpret quantitative data. The results of the data showed that the feasibility of testing 15 children aged 6–9 years was 95.3% with a very good category, the material expert test result was 98.6% with a very good category, and the media expert test result was 89.5% with a very good category. Therefore, it can be concluded that the ABJA (Aku Isa Basa Jawa) application is an application that is feasible to use as a medium to support the learning and preservation of Javanese language for elementary school or Madrasah Ibtidaiyah students.